Corelation of Social Media Exposure @pemkot_semarang and Intensity of Reference Group Communication with Desire of Tourism in Semarang - Atika Surya Nuraini; Djoko Setyabudi, S.Sos, MM (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Exposure is a state where the audience or readers exposed to communication messages contained in a mass media by means of senses such as feeling, hearing, and vision. Exposure to messages in social media into a media campaign that could potentially bring in the interest of individuals to travel to the city of Semarang. In addition, the intensity of the reference group communication also has the potential to have a relationship with interest in traveling to the city of Semarang. This study aims to determine the relationship of social media exposure instagram account @pemkot_semarang and intensity of group communication reference to the interest of traveling to the city of Semarang. The cornerstone in this study uses the theory of SOR (Stimulus - Organism - Response) and how groups influence consumer behavior. This type of research tends explanatory study with the technique of sampling in this research is done by simple random sampling technique. The total sample of 40 respondents with criteria that followers Intagram @pemkot_semarang account. Testing the hypothesis in this study using a test Kendals Tau_b with the help of SPSS applications. Based on the results of testing the hypothesis by using statistical test of Kendall's Tau_b showed that there is no significant relationship between exposure to media messages of social relations instagram account @pemkot_semarang (X1) with interest in traveling to the city of Semarang (Y). The second hypothesis test showed that there is a significant correlation between the intensity of the reference group communication (X2) with interest in traveling to the city of Semarang with a strong correlation coefficient.